Servant leadership and employee creativity: The mediating role of harmonious passion and psychological safety - Aneu YULIANEU; Muhamad Nurdin YUSUF (Tourism and Hospitality Management)
Purpose - This paper examines simultaneously mediating mechanisms through which servant leadership (SL) affects employee creativity (EC). Specifically, the authors test harmonious passion (HP) and psychological safety (PS) as the mediating paths through which servant leadership predicts employee creativity. Design/Methodology/Approach - Data were collected from 274 employees in seven four- and five-star hotels in Indonesia. A partial least squares structural equation modelling technique was used to estimate the measurement and structural models. Findings -The findings of this study indicate that managers should adopt servant leadership behaviors, which can improve employees’ psychological resources, such as harmonious creativity, passion, and psychological safety. Originality of the research - This study offers original insights into the emerging body of hospitality literature by presenting the initial empirical proof of the combined impact of harmonious passion and psychological safety in facilitating the influence of servant leadership on frontline employees’ creativity.